Meningkatkan Kualitas Produk Terhadap Loyalitas Pelanggan Pada Home Industry Karya Ayu Ciamis - Maulana, Yogi Sugiarto (JURNAL MANAJEMEN BISNIS, 2019)
Sales of banana chips tend to fluctuate, allegedly influenced by customers who switch to another company. This research was to determine and analyze the effect of product quality to customer loyalty. This study uses a quantitative approach explanatory. Using simple random sampling. The statistical method used is the product moment correlation. The results of the questionnaire are in either category. Coefficient correlation of 0.485 means that the relationship between variables in a category is. Influence of product quality to customer loyalty amounted to 23.5%. The test results hypothesis states that there is significant influence product quality on loyalty.